The life of Milarepa - Tsangnyon Heruka . (b, 2010)
The Life of Milarepa is one of the most beloved stories of the Tibetan people and a great literary example of the contemplative life. This biography, a dramatic tale from a culture now in crisis, can be read on several levels. A personal and moving introduction to Tibetan Buddhism, it is also a detailed guide to the search for liberation. It presents the quest for purification and buddhahood in a single lifetime, tracing the path of a great sinner who became a great saint. It is also a powerfully evocative narrative, full of magic, miracles, suspense, and humor, while reflecting the religious and social life of medieval Tibet.
Keywords: Mi-la-ras-pa, -- 1040-1123.; Lamas -- Biography. -- China -- Tibet Autonomous Region; China -- Tibet Autonomous Region